Antecedent of customer loyalty among Celcom user / Syaza Noor Azizi - Noor Azizi, Syaza (2015)
The study purpose is to identify the Antecedent of Customer Loyalty among Celcom User. 160 respondents were chosen from customer who came in to the Blue Cube for customer service activity. The findings shows that only two independent variables (trust and perceived service quality) have significantly relationship towards dependent variable; customer loyalty, remaining two variables (corporate image and switching cost) were found as not significant among Celcom user. Based on the results, the researcher found that perceived service quality have most relationship towards customer loyalty among Celcom user. The researcher suggests that Celcom should provide more loyalty program for customers. Besides that, improve the way to market the product and service will attract customer to join using Celcom. As for future researcher, the researcher suggest to increase the number of sample size, choose different service industry, use qualitative methods and to use other variables to relate with the customer loyalty.